THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE IN THE NATIONAL UNITY AND POLITICAL BODY OF BINJAI CITY - Nelly Rosa Hasibuan; Kiki Farida Ferine (Lafadz Jaya Publisher, 2023)
This study aims to analyze the Effect of Transformational Leadership on Employee Performance with Organizational Commitment as an intervening variable. The type of research used is associative quantitative. This research was conducted at the Office of National Unity and Community Protection in Binjai City. The population in this study was 50 employees consisting of 33 ASN employees and 17 honorary employees. The sample used was a saturated sample. The research model used is Path Analysis and the measurement tool is Smart PLS version 3.3.3. The results of this study are that Transformational Leadership has a positive and significant effect on Employee Performance. Transformational Leadership has a positive and significant effect on Organizational Commitment. Organizational Commitment has a positive and significant effect on Employee Performance.